Integrated process simulation of porcelain stoneware manufacturing using flowsheet simulation. (May 2021) - Alves, C.L.; De Noni Jr, A.; Janssen, R.; Hotza, D.; Rodrigues Neto, J.B.; Gómez González, S.Y.; Dosta, M.
Graphical abstract: Abstract: Integrated simulation of manufacturing plants plays crucial role in development of sustainable processes and optimized products. However, no investigation has been reported for the whole process chain of porcelain stoneware manufacturing. In this contribution, semi-empirical models of porcelain stoneware processing steps have been developed and implemented into Dyssol framework. By validation based on industrial and lab-scale experiments, the simulation has been applied for modeling and sensitivity analysis of the entire process. The simulation results are in a good agreement with experiments showing that the proposed modeling strategy has high potential to be used for future digital transformation in this sector.